Development Risk Management Mbah Buto Mojowarno Suspension Bridge on Regional Development - Ita Zeftin Trisnawati; Diah Ayu Restuti Wulandari (Journal of World Conference (JWC), 2022)
Infrastructure development in the form of roads and bridges is a government program in an effort to improve facilities and infrastructure. Infrastructure has a fairly strong relationship with social and environmental welfare for the development of a region. Bridges in Indonesia have progressed quite a lot. This is marked by the construction of several types of long bridges that connect one area to another. The construction of the Mbah Buto Suspension Bridge has a very positive role in increasing social activities, transportation facilities and improving the economy of the surrounding community. This study aims to determine the development of the area after the construction of the Mbah Buto Suspension Bridge. This research method uses descriptive quantitative method. The object of this research is the community around the construction site, using primary data sources in the form of questionnaire results, observations, and secondary data which includes supporting documents regarding development. The analytical method used is simple linear regression analysis using SPSS application in the form of validation test, reliability test, t test, and coefficient of determination test. The results of the study indicate that the Infrastructure Development in the form of the Mbah Buto Suspension Bridge has a very positive and significant role in social activities, transportation facilities and the economy of the surrounding community.